TRANSFORMATION OF ISLAMIC THOUGHT IN THE MODERN ERA: TRACES OF REFORM AND ITS CHALLENGES - Iin Inayatul Ummah; Usnia Usnia; Sholahuddin Al Ayubi; Andi Rosa (Adisam Publisher, 2025)
This article explores the evolution of Islamic thought within the framework of modernity, highlighting the signs of renewal initiated by Muslim thinkers and figures, as well as the challenges encountered during this journey. By employing a qualitative method and reviewing relevant literature, this research determined that integrating Islamic perspectives with a contextual approach could enhance Islamic education's role in fostering a better human civilization in today's world. Islamic thought has transitioned from a standard doctrinal framework to a conversational contextual framework that is better suited to the challenges of contemporary times. This renewal encompasses education, legal politics, Sufism, and technology, while encountering difficulties in striking a balance between tradition and modernity. In the views of Islamic scholars, Islamic education should prioritize a comprehensive approach that addresses not just intellectual dimensions but also spiritual, moral, and social elements.